(untitled) (Journal of humanities and social sciences exploratio, 2026)
As a dispute resolution mechanism stipulated in Chinese law, the domestic arbitration system has shown unique advantages in respecting the autonomy of the parties’ will, making a finalaward with a single arbitration, and having flexible procedures in recent years, and has developed rapidly. However, through an in - depth analysis of a typical arbitration award case, it can be found that there are still many problems in the current domestic arbitration system in practice, such as inconsistent arbitration trial rules, difficulties in correcting substantive errors caused by the finality of arbitration awards, insufficient transparency of arbitration procedures, and the deprivation of the parties’ right to autonomy of will by standard arbitration clauses. The existence of these problems not only restricts the development of the arbitration cause, but also affects the realization of social fairness and justice. Therefore, it is particularly necessary to deepen the reform of the domestic arbitration system. Based on the results of case analysis, this paper puts forward specific reform suggestions from the aspects of strengthening the leadership of the Party, strengthening administrative supervision, improving the internal and industry supervision and management systems, improving the quality of arbitration awards, and improving the judicial review and internal supervision mechanisms, aiming to provide theoretical support and practical guidance for improving the domestic arbitration system, promote the healthy and orderly development of the arbitration cause, and contribute to the construction of a socialist country under the rule of law.